GENETIC DISTANCE AND ITS RELATION TO THE PERFORMANCE OF INTRAHIRSUTUM Fl HYBRIDS (Biological Sciences - PJSIR, 2003)
Present stud,· ll'as i n i tiated to determi ne as ho\\ fa r genetic di sta nce i s irnpo11ant in the expression of hetero si s i n some cotton lea f cu rl virus resista nt and other i ntrah i rsutu m F, h ybrid s. Three  sets of  h> ·brids  ,,ere developed: J )  highl\' adapted Cotton Research Institute Sakrand (CRIS) lines crossed "ith  exotic li nes. 2)  CIUS  lines  crossed  \\ ith  Cotton  Research Insti tute Mul tan (CIM) li nes,  3)  the  CRIS  lines  crossed  with  CRIS li nes.  For  seed  cotton  vield.  n um ber  of bolls formed and fi bre length, the hybrids developed Crom exotic li nes expressed more percent of heterosi s than  hYbrids obtained   from   t he  crosses  of  CRIS vv"ith    CIM  or  CRIS  wit h   CRIS   lines  that  suggested   that  genetic  distance  is  ver, i m po11ant i n  the  expression  or heterosis  for  these  traits.  The  average  better  parent  hetero sis of  Exotic.  CIM, and   CRIS\                                                                  lwbrids  respecti vely were;  !(JG. 42.2 and 22.8 for seed cotton  yield. 77. J , 44.3 and 25.2%  for n um ber  of bolls and   5.8.4.8 and 4.6% for fi ber length. In respect to lint%. all the th ree sets of h1·brid s expressed negative  mean heterosi s whereas for seed i ndex, CR1S x CIM hvbrids expressed mea n heterosis of 1 3.5% against 4.7% of' CRIS x Exotics a nd 3.3% or CRlS x CRIS hybrid s. Consideri ng the performance of i nd j, ·id ual h,·brid s, CRJS-l 21 x CP-15 -12 wh ich gaYe maxi m um yield of 1 46.5 also prod uced highest boll s of 52. l , whereas hvbrid CRJS- J 68 x CIM-443 gin ned m axim um o[38.8% lint also gave highest seed i ndex oC 7.8 gm and  for fi bre length , CRlS-12 1  x CIM-443 pmd uced longer tibre of' 2